Impact of lesion calcification and hardness on periprocedural brain ischemia in patients with intracranial atherosclerotic disease undergoing angioplasty and stenting - Lin, Te-Ming; Sanz Cuesta, Borja Enrique; Yu, Kai-Wei; Yang, Chung-Han; Chung, Chih-Ping; Luo, Chao-Bao; Lirng, Jiing-Feng; Wu, Chia-Hung; Chang, Feng-Chi (Journal of neurointerventional surgery, 2025)
To evaluate the risk factors for periprocedural brain ischemic lesions (PBILs) in patients with severe intracranial arterial stenosis (ICAS) treated with percutaneous transluminal angioplasty and stenting (PTAS). We analyzed the data of a prospectively collected cohort of patients with severe ICAS in whom aggressive medical treatment had failed and who underwent PTAS with intracranial stents. Lesion calcification was identified on CT. The predilatation pressure (PP, the pressure at which the indentation of the angioplasty balloon disappears) and the balloon size were recorded. Periprocedural MR images were acquired before and after the procedure to identify any new brain ischemia. Logistic regression analyses were performed to assess differences between subjects with and without downstream ischemia. Receiver operating characteristic curve analysis was performed to determine threshold values for discriminating subjects with and without downstream PBILs. The data of 29 patients (mean±SD age 65.0±9.9 years, 21 men) were analyzed. Eighteen subjects (62%) had downstream PBILs on MRI. Calcified plaques (relative risk 11.7), a high PP during angioplasty (relative risk per atm 2.0), and a greater balloon diameter (relative risk per mm 4.0) were identified as risk factors for the presence of PBILs. Moreover, the presence of calcified plaques was associated with a greater PP (P=0.001). A PP threshold of 3.75 atm yielded the maximum sum of sensitivity and specificity. Some lesion characteristics including calcified plaques on CT and a high PP during angioplasty along with balloon diameter were identified as potential risk factors for PBILs after PTAS in patients with medically refractory ICAS.